L’évolution de la fiscalité minière fédérale de 1972 à 1978 - Bernard, Jean-Thomas (L'Actualité économique, 1980)
AbstractThis paper surveys the changes since 1972 in the federal tax laws applicable to the Canadian mining industry. Using a partial equilibrium model, we analyse the effect of these changes on the relative prices of the factors of production used by the mining firm. Changes in the provincial tax treatment of the mining industry are not considered. The effects on the mining firm of recent changes in tax legislation are compared to the no-tax and pre-1972 tax systems. A numerical illustration is used to summarize the total net impact of all the changes and to suggest their order of magnitude.The most striking conclusion to emerge from the analysis is that the net effect of the changes in tax legislation is relatively small due to offsetting provisions. It appears, however, that the tax burden of the industry has increased somewhat as a result of the recent federal changes. In addition, the numerical illustration shows that, in general, the corporate income tax system applied to the Canadian mining industry has consistently favoured the use of capital over current factors of production. Changes in mineral taxation have not altered this result.